Ambulatory Training Program to Expand Procedural Skills in Primary Care. (June 2019) - Fortuna, Robert J.; Marston, Bethany; Messing, Susan; Wagoner, Gunnar; Pulcino, Tiffany L.; Bingemann, Todd; Caiola, Enrico; Scofield, Steven; Nead, Karen; Robbins, Brett W
Introduction: Outpatient procedures are an important component of primary care, yet few programs incorporate procedural training into their curriculum. We examined a 4-year procedural curriculum to improve understanding of ambulatory procedures and increase the number of procedures performed. Methods: A total of 56 resident and 8 faculty physicians participated in a procedural curriculum directed at joint injections (knee, shoulder, elbow, trochanteric bursa, carpal tunnel, wrist, and ankle), subdermal contraceptive insertion/removal, skin biopsies, and ultrasound use in primary care. We administered annual surveys and used generalized estimating equations to model changes. Results: Across the 4 years, there was an average 96% response rate. Mean comfort level with the indications for procedures increased for both resident (62.5 to 78.8; P < .0001) and faculty physicians (61.5 to 94.8; P < .0001). Similarly, mean comfort with performing procedures increased for both resident (32.1 to 62.3; P < .0001) and faculty physicians (42.2 to 85.4; P < .0001). Residents' comfort level performing procedures increased for all individual procedures measured. The mean number of procedures performed per year increased for resident (1.9 to 8.2; P < .0001) and faculty physicians (14.7 to 25.2; P = .087). Conclusions: A longitudinal ambulatory-based procedural curriculum can increase resident and faculty physician understanding and comfort performing primary-care-based procedures. This, in turn, increased the total number of procedures performed.